Natural product-based pharmacological studies for neurological disorders - Puri, Vivek; Kanojia, Neha; Sharma, Ameya; Huanbutta, Kampanart; Dheer, Divya; Sangnim, Tanikan (Frontiers in Pharmacology, 2022)
The prevalence of central nervous system disorders and diseases is expected to rise sharply in the coming years, in part because of the world's ageing population. Effective medicines have not been successfully translated from the laboratories to the clinic in the development of drugs for the central nervous system. Inadequate knowledge on brain, pharmacokinetics and dynamics errors in preclinical studies, challenges with clinical trial design, the complexity and variety of human brain illnesses, and variations in species are some of the potential scenarios. Neurodegenerative diseases are multifaceted and lack identifiable etiological components, drugs developed to treat them have not met the requirements of those who anticipated for treatments. Natural therapeutic adjuvants that are both safe and effective have been in high demand for a long time because of this. For the treatment of neurodegenerative diseases and other memory-related problems, many herbal and natural items have been used in the Ayurvedic medical system. Anxiety, depression, Parkinson's, and Alzheimer's diseases, as well as a plethora of other neuropsychiatric disorders may benefit from the use of plant and food-derived chemicals that have been shown to have antidepressant or antiepileptic properties. We have summarized the present level of knowledge on natural products based on topological evidence, bioinformatics analysis, and translational research in this review. We have also highlighted some clinical research or investigation that will help us in selecting natural products for the treatment of neurological conditions.